2012
DOI: 10.4274/jcrpe.725
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gene Mutations Associated with Familial Normosmic Idiopathic Hypogonadotropic Hypogonadism

Abstract: Objective: Normosmic idiopathic hypogonadotropic hypogonadism (nIHH) is characterized by failure of initiation or maintenance of puberty due to insufficient gonadotropin release, which is not associated with anosmia/hyposmia. The objective of this study was to determine the distribution of causative mutations in a hereditary form of nIHH.Methods: In this prospective collaborative study, 22 families with more than one affected individual (i.e. multiplex families) with nIHH were recruited and screened for genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Nevertheless, the possibility of a more remote common ancestry cannot be totally discarded. The p.R139H has also been reported in five other unrelated cases of different geographic origins worldwide, which were not evaluated here, and further studies would be necessary to determine if they too have a common ancestor (12, 30, 44, 47, 48). On the other hand, another mutation affecting the same codon (p.R139C) was described in two cases, raising the possibility that this may be a hotspot region (48, 49).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the possibility of a more remote common ancestry cannot be totally discarded. The p.R139H has also been reported in five other unrelated cases of different geographic origins worldwide, which were not evaluated here, and further studies would be necessary to determine if they too have a common ancestor (12, 30, 44, 47, 48). On the other hand, another mutation affecting the same codon (p.R139C) was described in two cases, raising the possibility that this may be a hotspot region (48, 49).…”
Section: Discussionmentioning
confidence: 94%
“…Large-scale screening indicates that GNRHR mutations account for 3.5-16% of sporadic cases of nIHH and up to 40% of familial cases of nIHH [15]. In our cohort, Gurbuz et al [16] previously identified GNRHR gene mutations in 7 of 22 families (31.8%) with nIHH. Mutations in GNRH1 are extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Chan [4] estimated the prevalence of GNRH1 mutations at 0.33% based on 600 pedigrees collectively screened by various groups. Although it has been repeatedly observed that mutations are less frequent in the genes encoding the ligands than in their corresponding cognate receptor [4,16], still, contrasting frequency of GNRH1 and GNRHR mutations has been found to be striking. Nevertheless, it should also be noted that the length of the coding sequences of the ligands are usually much shorter than their cognate receptors, making it less likely to suffer from mutations, as in GNRH1/GNRHR pair.…”
Section: Discussionmentioning
confidence: 99%
“…The study of IGD in multiplex families from geographically delineated populations with high rates of endogamy has been another highly fruitful method of IGD gene discovery (69). The gene coding for kisspeptin receptor 1 (KISS1R) was discovered using linkage analysis in an endogamous pedigrees with multiple affected Bedouin family members displaying nIHH (70,71).…”
Section: Endogamous Pedigrees Lead To the Discovery Of Recessive Imentioning
confidence: 99%